Use of lattice functions at definition of spectral consisting of nonsinusoidal periodic signals - Tsapko G. P. Gennady Pavlovich (2005, 2005)
Use of lattice functions for processing the information by a method of discrete Fourier transformation, a method of instant spectral density and a method of synchronous detecting allows to reduce general volume of calculations significantly. Reduction of volume of calculations allows to raise speed and to expand frequency a range of researches significantly.